Initial Public Offering: Perlindungan Hukum Pemegang Saham Minoritas dan Pengaruh Terhadap Kinerja Perusahaan - Jasmine, Alifia; Yasmine, Azmi; Sharfina, Nurul Hulwanita; Fathhurrohmah, Aisyah Hanifah (Jurnal Hukum & Pembangunan, 2024)
This research discusses Initial Public Offerings: Legal Protection of Minority Shareholders and Its Influence on Company Performance. This research aims to provide knowledge to the public regarding legal protection for minority shareholders and its influence on company performance from a national legal perspective. This type of research is normative research with the research approach used is a legal and conceptual approach. The research results show that: (1) The process of attracting investors to invest their capital cannot be separated from good regulations and legal certainty. Basically there are 2 (two) types of capital investment, namely direct investment and capital investment. indirect (portfolio investment) as regulated in Article 2 of the Capital Markets Law, (2) It can be seen that the financial performance trend shows an increase in terms of profitability, liquidity and growth ratios but there is a decrease in terms of liquidity and activity ratios. The implications of this research can be used as a source of knowledge for the public, especially regarding Initial Public Offerings regarding legal protection for minority shareholders and also its impact on company performance.